The mechanism of mammalian peroxidase destruction of invasive microbes - Razvan Puf; Michael L. Smith; Aatto Laaksonen (PLoS ONE, 2026)
We calculated the internal energies (ΔE) for the breakdowns of HOI, HOBr and HOCl for the first time using the principles of molecular orbital theory. The release of atomic oxygen (ATOX) from all three molecules was estimated being from 43.3 (HOCl) to 64.1 (HOI) kcal mol −1 . These internal energies are much less than the inputs required for hydroxyl anion and cationic halide productions which range from 315.0 (HOI) to 381.1 (HOCl) kcal mol −1 . These results answer the puzzle concerning the fates of the products from the halide oxidations by peroxidases. The active species were thought to be the hypohalous acids themselves or the cationic halide but ATOX has never been considered. ATOX is an electron pair accepter and an incredibly destructive species which is observed only in high energy systems. Our results have implications for mammalian immunology because the final steps for microbe disposal in mammals are destructions by one of three peroxidases; lactoperoxidase (LPO), eosinophil peroxidase (EPO) or myeloperoxidase (MPO). These all utilize H 2 O 2 and one of the halide ions; I − (LPO), Br − (EPO) or Cl − (MPO) to biosynthesize HOI, HOBr and HOCl, respectively. The low energies required for ATOX liberation from hypohalous acids explains why these are the preferred products of important mammalian peroxidases. For example, LPO is an integral enzyme of mammalian airway defence and enhanced nutritional iodine intake encourages liberal biosynthesis of HOI, which is immediately lethal to all microbes tested in vitro and in vivo.